Cross-dehydrogenative coupling reactions between arenes (C–H) and carboxylic acids (O–H): a straightforward and environmentally benign access to O-aryl esters. Issue 30 (31st May 2019) - Arshadi, Sattar; Banaei, Alireza; Monfared, Aazam; Ebrahimiasl, Saeideh; Hosseinian, Akram
Abstract : Transition-metal catalyzed cross-dehydrogenative-coupling encompass atom economical methods for the construction of various carbon–carbon and carbon–heteroatom bonds by combining two C(X)–H (X = heteroatom) bonds. Abstract : Transition-metal catalyzed cross-dehydrogenative-coupling reactions encompass highly versatile and atom economical methods for the construction of various carbon–carbon and carbon–heteroatom bonds by combining two C(X)–H (X = heteroatom) bonds. Along this line, direct acyloxylation of C–H bonds with carboxylic acids has emerged as a powerful and green approach for the synthesis of structurally diverse esters. In this focus-review we will describe recent progress in direct esterification of aromatic C–H bonds with special emphasis on the mechanistic features of the reactions. Literature has been surveyed until the end of February 2019.